Recurrent failure of ART, thrombosis and thrombophilia - J. Kh. Khizroeva; A. S. Antonova; E. S. Egorova; N. A. Makatsariya (Акушерство, гинекология и репродукция, 2024)
In recent years, the number of risk factors for thrombosis associated with pregnancy has increased substantially due to the active introduction of new medical technologies not used 30 years ago or because their role in emerging thrombosis has not been studied, e.g., during pregnancy after assisted reproductive technologies (ART) particularly in vitro fertilization (IVF). The risk of venous thromboembolic complications (VTEС) related to ovarian hyperstimulation during ART is often overlooked. We present the case of a 37-year-old woman who developed thrombosis of the right internal jugular vein 3 weeks after embryo transfer within the IVF protocol. Ovarian hyperstimulation during hormonal IVF protocols provokes procoagulant changes in the hemostasis and fibrinolysis system able to result in venous and arterial thrombosis. The localization of VTEС typical to ART is more often located in the internal jugular vein being accompanied by neck pain and edema. Thrombosis risk factors should be assessed in all women in the IVF program, and appropriate thromboprophylaxis should be carried out to all high risk subjects.